Pairing symmetries of several iron-based superconductor families and some similarities with cuprates and heavy-fermions - Das Tanmoy (EPJ Web of Conferences, 2012)
We show that, by using the unit-cell transformation between 1 Fe per unit cell to 2 Fe per unit cell, one can qualitatively understand the pairing symmetry of several families of iron-based superconductors. In iron-pnictides and iron-chalcogenides, the nodeless s±-pairing and the resulting magnetic resonance mode transform nicely between the two unit cells, while retaining all physical properties unchanged. However, when the electron-pocket disappears from the Fermi surface with complete doping in KFe2As2, we find that the unit-cell invariant requirement prohibits the occurrence of s±-pairing symmetry (caused by inter-hole-pocket nesting). However, the intra-pocket nesting is compatible here, which leads to a nodal d-wave pairing. The corresponding Fermi surface topology and the pairing symmetry are similar to Ce-based heavy-fermion superconductors. Furthermore, when the Fermi surface hosts only electron-pockets in KyFe2-xSe2, the inter-electron-pocket nesting induces a nodeless and isotropic d-wave pairing. This situation is analogous to the electron-doped cuprates, where the strong antiferromagnetic order creates similar disconnected electron-pocket Fermi surface, and hence nodeless d-wave pairing appears. The unit-cell transformation in KyFe2-xSe2 exhibits that the d-wave pairing breaks the translational symmetry of the 2 Fe unit cell, and thus cannot be realized unless a vacancy ordering forms to compensate for it. These results are consistent with the coexistence picture of a competing order and nodeless d-wave superconductivity in both cuprates and KyFe1.6Se2.